Indonesian Electoral Democracy: Between Pancasila and the Global Perspective - Hasibuan, Ricky (Indonesian Journal of Pancasila and Global Constitutionalism, 2024)
Indonesia's electoral democracy stands at a crossroads, balancing the foundational principles of Pancasila with global democratic norms and practices. This paper examines the dynamics shaping Indonesia's electoral democracy, exploring the tensions and harmonies between Pancasila's ideological framework and international democratic standards. The analysis begins by contextualizing the evolution of Indonesia's electoral democracy, tracing its roots in the post-authoritarian era and the subsequent institutional reforms. It then delves into the core principles of Pancasila, emphasizing its emphasis on collective welfare, social justice, and national unity. Drawing on comparative insights from global electoral democracies, the paper evaluates Indonesia's electoral system in light of international standards of electoral integrity, transparency, and inclusivity. It identifies areas of alignment and dissonance between Pancasila's ethos and global democratic benchmarks. Furthermore, the paper scrutinizes the role of Pancasila in shaping electoral processes, political parties, and voter behavior. It explores how Pancasila's emphasis on consensus-building and inclusivity intersects with the competitive nature of electoral politics. Through this analysis, the paper contributes to a nuanced understanding of Indonesia's electoral democracy, highlighting the complexities of navigating between Pancasila's indigenous values and global democratic imperatives. It underscores the importance of balancing national identity with international best practices to strengthen the legitimacy and effectiveness of Indonesia's democratic institutions.